Bridging the Intention–Behavior Gap in Organic Food Consumption: An Integrative Systematic Review of Emotion, Green Altruism, and Psychological Distance - Ari Apriani; Setyo Riyanto; Rina Astini; Mas Wahyu Wibowo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Organic food consumption has grown alongside increasing consumer concern for health, environmental sustainability, and ethical responsibility. Yet favorable attitudes do not consistently translate into actual purchasing behavior, indicating that the intention–behavior gap in this domain cannot be explained by rational evaluations alone. This study conducts a systematic literature review to develop an integrative psychological explanation of how emotion, green altruism, and psychological distance shape organic food consumption. Following PRISMA 2020, the review analyzed 35 peer-reviewed articles indexed in Scopus, Web of Science, and ScienceDirect and published between 2015 and 2025. The findings show that emotional mechanisms, particularly anticipated pride, guilt, and emotional attachment, commonly strengthen purchase intention by increasing perceived personal relevance, moral meaning, and self-consistency. Green altruism supports organic food consumption by framing it as an environmentally and socially responsible act, although its influence varies across contexts, consumer segments, and product categories. The reviewed evidence further indicates that psychological distance functions mainly as a framing and moderating mechanism that shapes whether emotional and altruistic motives are perceived as immediate, concrete, and behaviorally actionable. Across the reviewed studies, emotional and moral mechanisms more consistently predict intention than repeated purchase behavior, while trust, norms, and message framing help explain empirical inconsistencies. Overall, this review advances an integrative framework for explaining organic food consumption beyond rational choice and provides directions for future research on sustainable consumption behavior.